1986
DOI: 10.1021/i300024a012
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroepoxy resin for moisture vapor barrier coating and other applications

Abstract: A new fluoroepoxy resin has been developed that can be processed as a conventional thermoset resin yet possesses some of the unique properties of the well-known thermoplastic fluoropolymers. Its moisture vapor transmission rate and moisture absorption were found to be unusually low. In general, the transmission rates were Inversely proportional to the fluorine content of the materials tested. The fluoroepoxy was shown to be an excellent moisture vapor barrier coating or sealant and an effective adhesive to bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…3 5 One of the many efforts to outcome these deficiencies consists in the introduction of fluorine (F)-containing groups in backbone or side chain of the polymers in order to gain chemical stability, low dielectric constant, low dissipation factor, and low moisture absorption. 6 9 The efficiency of this method arises from the special characteristics of F, such as low polarizability, small dipole, hydrophobicity and oxidization resistance as well as relative larger free volume. 10,11 In the same time, it has been found that the method used in their synthesis (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 5 One of the many efforts to outcome these deficiencies consists in the introduction of fluorine (F)-containing groups in backbone or side chain of the polymers in order to gain chemical stability, low dielectric constant, low dissipation factor, and low moisture absorption. 6 9 The efficiency of this method arises from the special characteristics of F, such as low polarizability, small dipole, hydrophobicity and oxidization resistance as well as relative larger free volume. 10,11 In the same time, it has been found that the method used in their synthesis (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Lee and Griffith 8 first reported the synthesis of F-containing epoxy resins. Since then, a lot of efforts have been made to develop novel epoxy resin materials with chemical structures that translate into improved properties.…”
Section: Introductionmentioning
confidence: 99%